2020
DOI: 10.3389/fonc.2020.00333
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Immune-Related Genes as Potential Marker of Prognosis in Breast Cancer

Abstract: The tumor microenvironment (TME) is a heterogeneous system that contributes to breast cancer progression. The Cancer Genome Atlas (TCGA) database provides global gene expression profiling data for further analysis of various malignancies, including breast cancer. Based on the ESTIMATE algorithm, immune and stromal scores were calculated according to immune or stromal components in the TME. We divided breast cancer cases into high-and low-score groups and identified differentially expressed genes (DEGs) that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…Firstly, we observed the statistically significant difference between two age groups with regard to patient outcomes in the IntCl1, possibly owing to immunerelated genes. Indeed, many previous studies were of interest to the interaction between the immune system and age factor in BRCA (Fuentes et al, 2017;Li et al, 2020;Xu et al, 2020). Especially, Li et al (2020) indicated that there was a positive correlation of aging with i) the lower median immune/stromal scores and ii) the lower OS of BRCA patients.…”
Section: Prognostic Factor Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we observed the statistically significant difference between two age groups with regard to patient outcomes in the IntCl1, possibly owing to immunerelated genes. Indeed, many previous studies were of interest to the interaction between the immune system and age factor in BRCA (Fuentes et al, 2017;Li et al, 2020;Xu et al, 2020). Especially, Li et al (2020) indicated that there was a positive correlation of aging with i) the lower median immune/stromal scores and ii) the lower OS of BRCA patients.…”
Section: Prognostic Factor Identificationmentioning
confidence: 99%
“…Indeed, many previous studies were of interest to the interaction between the immune system and age factor in BRCA (Fuentes et al, 2017;Li et al, 2020;Xu et al, 2020). Especially, Li et al (2020) indicated that there was a positive correlation of aging with i) the lower median immune/stromal scores and ii) the lower OS of BRCA patients. In contrast, an insignificant correlation of the IntCl2's patient survival with age factor was monitored.…”
Section: Prognostic Factor Identificationmentioning
confidence: 99%
“…lncRNAs are receiving increasing attention because of their close association with tumorigenesis [15,16]. Moreover, the immune system plays a vital role in tumor development and progression [17,18]. Thus, immune-related lncRNAs may prove to be useful not only as potential prognostic biomarkers but could also provide novel therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…With the in-depth researches on lncRNAs and the immune system [21][22][23][24], scholars have realized that immune-related lncRNAs may prove to be useful not only as potential prognostic biomarkers but could also provide novel therapeutic options. Nevertheless, the lack of validation cohorts is a limitation for the proper evaluation of the prognostic merit of potential biomarkers.…”
Section: Discussionmentioning
confidence: 99%